2017
DOI: 10.1038/eye.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary cotinine level is associated with a trend toward more myopic refractive errors in Korean adolescents

Abstract: PurposeTo investigate the association between urinary cotinine levels as an objective biological marker for exposure to nicotine and refractive status.Patients and methodsThis cross-sectional study analyzed data from the Korea National Health and Nutrition Examination Survey between 2008 and 2011. A total of 1139 Korean adolescents aged 12-18 years were enrolled. Urinary cotinine concentrations and other potential risk factors for myopia were examined. Correlation analyses and multivariate regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…A similar protective relationship was reported in a sample from a pediatric ophthalmology clinic, which largely persisted after adjustment for a range of factors including child's near work activity and parental myopia and education [167]. A detailed study from South Korea reported consistent results for exposure to passive smoke estimated from urinary cotinine level [168], supporting the suggestion that nicotinic pathways are involved in the regulation of eye growth. In contrast, Rahi et al reported a positive association between maternal smoking in early pregnancy and more myopia [47].…”
Section: Smokingsupporting
confidence: 70%
“…A similar protective relationship was reported in a sample from a pediatric ophthalmology clinic, which largely persisted after adjustment for a range of factors including child's near work activity and parental myopia and education [167]. A detailed study from South Korea reported consistent results for exposure to passive smoke estimated from urinary cotinine level [168], supporting the suggestion that nicotinic pathways are involved in the regulation of eye growth. In contrast, Rahi et al reported a positive association between maternal smoking in early pregnancy and more myopia [47].…”
Section: Smokingsupporting
confidence: 70%
“…The long-term outcome of CNV is poor if left untreated. In a 10-year follow-up study of 25 patients with myopic CNV, visual acuity deteriorated to 20/200 or worse in 89% and 96% of eyes in 5 years and 10 years, respectively [168].…”
Section: Management Of Myopic Choroidal Neovascularizationmentioning
confidence: 99%
“…Myopic choroidal neovascularization (myopic CNV) is the second most common cause of CNV after age-related macular degeneration (AMD) [167,168]. It is one of the most sight-threatening complications of pathological myopia [119,169] and is the most common cause of CNV in those 50 years or younger [167], with significant social and economic burden.…”
Section: Management Of Myopic Choroidal Neovascularizationmentioning
confidence: 99%
See 2 more Smart Citations